Extraction techniques in food industry: Insights into process parameters and their optimization. (August 2022) - Sridhar, Adithya; Vaishampayan, Vijay; Senthil Kumar, P.; Ponnuchamy, Muthamilselvi; Kapoor, Ashish
Abstract: This review presents critical evaluation of the key parameters that affect the extraction of targeted components, giving due consideration to safety and environmental aspects. The crucial aspects of the extraction technologies along with protocols and process parameters for designing unit operations have been emphasized. The parameters like solvent usage, substrate type, concentration, particle size, temperature, quality and storage of extract as well as stability of extraction have been elaborately discussed. The process optimization using mathematical and computational modeling highlighting information and communication technologies have been given importance aiming for a green and sustainable industry level scaleup. The findings indicate that the extraction processes vary significantly depending on the category of food and its structure. There is no single extraction method or universal set of process conditions identified for extracting all value-added products from respective sources. A comprehensive understanding of process parameters and their optimization as well as synergistic combination of multiple extraction processes can aid in enhancement of the overall extraction efficiency. Future efforts must be directed toward the design of integrated unit operations that cause minimal harm to the environment along with investigations on economic feasibility to ensure sustainable extraction systems. Highlights: Effect of extraction process parameters is examined. Modeling and optimization techniques can aid in improving efficiency. Techno-economic, safety and environmental aspects of processes should be considered. Hybrid methods can lead to sustainable technologies.